Design concepts for DNA-encoded library synthesis. (1st July 2021) - Zhang, Y.; Clark, M.A.
Graphical abstract: Abstract: An approach of building block (BB) inclusivity and atom efficient library schemes deliver the quality and diversity of DNA-encoded libraries best suited for small molecule drug discovery. In this Perspective, we offer key learnings in DEL design from a decade's worth of DEL-driven screening.